Immunohistochemistry combined with NGS to assist the differential diagnosis of multiple primary lung cancer with lymph node metastasis: a case report - Liu, Chang; Zhang, Shuai; Yang, Hong; Bai, Yu; Shen, Yanru; Ren, Yi (Frontiers in Oncology, 2023)
In recent years, the incidence of synchronous multiple primary lung cancers (MPLCs) has gradually increased. Surgery is the preferred treatment for these patients. There are great differences in the driving genes between individual tumors in patients with MPLC, and tumors with targeted mutations do not represent other tumors, which challenges the selection of targeted therapies for patients with MPLC. Driving mutations in each lesion after surgery are crucial for establishing accurate pathological staging and subsequent treatment strategies. There are some mutated genes in the lymph nodes of postoperative metastatic MPLCs, and the tumor cell count/DNA concentration is low, which limits the next-generation sequencing (NGS) detection effect. A combination with immunohistochemistry to determine the source of metastasis may be a better choice. This study reports a rare case of lung cancer with double primary adenocarcinomas of the lung combined with 10 groups of lymph node metastases. The source of metastasis was identified using immunohistochemistry combined with NGS to guide postoperative adjuvant treatment. We hope that this case report can provide new ideas for the identification of MPLCs and assist in their diagnosis and individualized treatment. In addition, the combination specific immunohistochemistry and NGS seems to be an effective identification method. This approach can provide clinical benefits; however, this still requires further exploration through studies with large sample sizes.